EFFECT OF CHEMICAL ELEMENTS ON THE FUNCTIONAL STATE OF THE CARDIOVASCULAR SYSTEM - Анна Валериевна Дубовая (The Publishing House Medicine and Enlightenment, 2016)
In the work the results of research on the impact of macro- and micronutrients in the functional state of the cardiovascular system are generalized. The studies often are experimental in nature, while the data from clinical trials are scarce, especially in children. The most perspective is represented finding-out of influence of pathological concentration of trace elements on occurrence pathology of cardiovascular system.